2 Differential effects of left ventricular hypertrophy on coronary haemodynamics in aortic stenosis and hypertension. (4th June 2021) - Ramakrishnan, Anenta; Hadjiloizou, Nearchos; Ahmad, Yousif; Sen, Sayan; Malik, Iqbal; Parker, Kim; Francis, Darrel; Hughes, Alun; Davies, Justin; Mayet, Jamil
Abstract : Background: Hypertension and aortic stenosis(AS) are the commonest causes of left ventricular hypertrophy (LVH) and share similar pathophysiological features. Whilst an increase in resting coronary blood flow (per gram of LV) has been observed in AS, reduced resting coronary blood flow (per gram of LV) has been observed in hypertension. Aim: We aimed to compare coronary flow patterns in subjects with left ventricular hypertrophy and aortic stenosis, in subjects with left ventricular hypertrophy and hypertension, and in subjects without left ventricular hypertrophy or hypertension. Methods: We recruited 31 subjects (mean age 63, 18 female). 10 subjects had LVH and severe AS, 11 had LVH and hypertension and 10 had no LVH and no AS, with LVH defined on echocardiography. Simultaneous invasive pressure and Doppler velocity measurements in each of the left coronary arteries were taken. We performed 'wave intensity analysis', which is a method for separating the coronary flow pattern in terms of 'waves' that are generated proximally (by the aorta and systemic arteries) and distally (by the myocardial microcirculation). Results: Mean resting coronary flow per gram of tissue ( figure 1 ) was increased in participants with LVH secondary to AS (1.62±0.60ml/min/g) and reduced in participants with LVH secondary to HT(0.49±0.27ml/min/g), compared to participants with no LVH and no AS (1.47±0.73ml/min/g). Wave 6 ( figure 2 ) is the backwards decompression wave (BDW) and is particularly important for myocardial perfusion. The BDW corresponds to the diastolic 'suction' of blood down the coronary arteries during myocardial relaxation. The energy of the BDW was increased in LVH secondary to AS (31.1 x10 3 Wm- 2 s- 2 ) but was reduced in LVH secondary to HT (12.3x10 3 Wm- 2 s- 2 ) (p<0.05), compared to participants with no LVH and no AS (14.3x10 3 Wm- 2 s- 2 ). The energy of the BDW correlated with LV cavity pressure (r=0.84, p<0.001) and diastolic time (r=-0.62, p<0.001) only in LVH secondary to AS participants. In contrast, the BDW correlated with LV mass (r=-0.49, p=0.03) in participants with LVH secondary to HT and with no LVH and no AS, but not in participants with LVH secondary to AS. Conclusions: In hypertension, LVH is associated with reduced mean coronary flow and reduced myocardial 'suction' during diastole. However, in AS, the large pressure gradient between the LV cavity pressure and the aorta results in a large contractile force which is generated in systole and then released in diastole. This large diastolic force overwhelms any local impairment caused by the hypertrophied myocardium and contributes to high resting coronary flow in LVH that is secondary to AS, compared to LVH that is secondary to hypertension. Conflict of Interest: None